Improving Government and Community Synergy in Rabies Control and Overcoming in Tomohon City: Study at the Health and Agriculture Department - Nina Elisabet Lelet; Femmy M. G. Tulusan; Grace J. Waleleng (Journal La Bisecoman, 2024)
Rabies, known as mad dog disease, is an acute infectious disease that can attack humans. To date, many people have been affected by rabies, including those in Tomohon City. This research was conducted to analyze the synergy between the government and the community in controlling rabies in Tomohon City. The research design used is qualitative. Research findings show that Tomohon City is one of the cities in Indonesia that is not yet free from rabies. The policies set by the Tomohon City Government have not been able to suppress rabies cases. Weak communication and coordination from related agencies and lack of community support are the main causes. The strategy that needs to be implemented is related to problem solving, the role of government and communication networks. Therefore, it is necessary to strengthen border area control over the traffic of animals that transmit rabies, carry out direct outreach and education to the public about the prevention, control and management of rabies, impose sanctions on market traders who still sell meat from animals that transmit rabies without health documents and increase cooperation and coordination between the Subdistrict Government, Subdistrict Government, and related Government Agencies as well as with the Community.